Asynchronous Bilateral Ureteric-Arterial Fistula: Diagnosis and Treatment. (3rd May 2021) - Pepe, Pietro; D'Arrigo, Letterio; Patane', Domenico; Pepe, Ludovica; Candiano, Giuseppe; Pennisi, Michele
Abstract : A 48-year-old woman submitted to anterior exenteration plus ileal-cutaneous conduit for metastatic cervical cancer during the change of the ureteral stent showed massive bleeding in the left ureter. A selective intra-arterial angiography showed a fistula between the ureter and the left common iliac artery that the interventional radiologist quickly repaired by inserting a vascular endoprosthesis. Six months later, gross hematuria secondary to right ureter-iliac fistula occurred again and a second endoprosthesis was inserted. Asynchronous bilateral ureteric stent-related vascular fistula is an uncommon scenario, but it should be suspected in the presence of hematuria following ureteral stent replacement.